Villainess Protagonists’ Performative Acts as the Representation of Modern Femininity - Chertian, Vivian Graciela (Bina Nusantara University, 2022)
The research discussed a different representations of femininity through the villainesses and heroines in two Korean webtoons (web cartoons). Traditionally, villainesses were depicted as undesirable antagonists as they did not fit into the frame of traditional femininity or were merely viewed as sexually attractive. However, the traditional aspects of femininity were now contested by the villainess protagonists. Utilizing Butler’s theory of gender performativity along with Kress and van Leeuwen’s visual analysis, the protagonists’ and antagonists’ thoughts, actions, and appearance were analyzed. A descriptive qualitative analysis was conducted on two webtoons, The Villainess Reverses the Hourglass, and It Looks Like I’ve Fallen into the World of a Reverse Harem Game. The studied data are selected from chapters 1-45 in each webtoon. The results show that the villainess protagonists are depicted as more independent, have more power, and occasionally dress in a masculine way, while the heroines-turned-antagonists are illustrated as a dependent, lack power, and always dressed femininely. In this case, the heroines-turned-antagonists’ traits represent Korea’s traditional notion of femininity. Meanwhile, the villainess protagonists possess traits opposing the heroines’ traits. Positioning the villainesses as protagonists and heroines as antagonists show a clash of modern vs. traditional notion of femininity, and putting the ‘villainesses’ as the desirable protagonists imply how their representation of femininity is considered more favorable in the modern context.